Aplikasi Pupuk Organik Cair Berbasis Limbah Kulit Kopi terhadap Pertumbuhan Vegetatif Bibit Kopi Arabika - Nico Dwi Saputro; Edi Wiraguna (Hidroponik : Jurnal Ilmu Pertanian Dan Teknologi Dalam Ilmu Tanaman, 2025)
Coffee production generates large amounts of solid waste, particularly coffee pulp, which can lead to environmental pollution if not properly managed. This study investigates the utilization of coffee pulp waste as a liquid organic fertilizer (LOF) and its effect on the growth of Arabica coffee seedlings (Coffea arabica L.). The experiment was conducted using a randomized complete block design (RCBD) with five treatments (0, 10, 20, 30, and 40 ml/L of LOF) and five replications. Observations were made on seedling height, stem diameter, and number of leaves over a four-month period. The results showed that the application of LOF had a significant effect on plant height and number of leaves. The highest increase in height and leaf count was observed in the 30 ml/L treatment, while the 40 ml/L treatment showed a slight decline, possibly due to nutrient oversaturation. However, stem diameter did not show a statistically significant difference among treatments. Correlation analysis indicated a strong positive relationship between plant height and leaf number (r = 0.800), suggesting synchronized vegetative growth. These findings demonstrate the potential of coffee pulp LOF as an eco-friendly alternative to chemical fertilizers in coffee seedling nurseries. Further research is recommended to evaluate long-term effects and optimal dosages for different growth stages.